Fractional robust PID control of a solar furnace. (November 2016) - Beschi, M.; Padula, F.; Visioli, A.
Abstract: This paper deals with the fractional control of the temperature in solar furnace plants. As for all the concentrated solar plants, the solar furnace can be modeled as a nonlinear system, where the dynamics strongly depends on the operating temperature. However, to improve the effectiveness of this technology, the control system should guarantee an acceptable performance independently from the operating point. In order to overcome this problem, we propose to use the generalized isodamping technique, where we aim at achieving the invariance of the control loop phase margin with respect to the plant operating point through a properly designed fractional-order proportional-integral-derivative controller. A gain-scheduling algorithm is also introduced to cope with wide plant variations. Simulation and experimental results show the effectiveness of the proposed methodology.